PERAN LEMBAGA PEMASYARAKATAN DALAM MEMENUHI HAK-HAK NARAPIDANA DISABILITAS - Subroto, Mitro; Fauzan, Lathif Nur (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: In following their guidance and life in correctional institutions, prisoners with disabilities often face challenges and obstacles. This research aims to analyze the role of correctional institutions in fulfilling the rights of prisoners with disabilities in Indonesia, especially in terms of accessibility, legal protection services, and rehabilitation services. This research approach uses descriptive qualitative methods and normative legal approaches, this research uses library sources and secondary data as well as document studies regarding applicable policies to analyze the case at hand. Based on the results of the research, although there are regulations governing the fulfillment of the rights of prisoners with disabilities, their implementation in the field has not been fully implemented. There are still many obstacles such as limited supporting facilities, lack of knowledge and training from officers, and lack of specific coaching programs for prisoners with disabilities. This research also found that there is a misalignment between the policies implemented and the basic needs of prisoners with disabilities, resulting in the low quality of services they receive. Therefore, this research suggests developing more inclusive correctional policies, improving the quality of correctional officers, and improving infrastructure to ensure the needs and rights of prisoners with disabilities are met. The output of this research is expected to be a guide for policy makers and correctional officers in fulfilling the rights of prisoners with disabilities in correctional institutions.Keywords: Prisoners, disability, correctional institutions, human rights.